1996
DOI: 10.1016/s0006-3495(96)79238-x
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating inclusion complexes from host molecules by tapping-mode atomic force microscopy

Abstract: Tapping-mode atomic force microscopy imaging under different cantilever vibration amplitudes has been used to differentiate the host beta-cyclodextrin nanotubes from retinal/beta-cyclodextrin inclusion complex nanotubes. It was observed that both compounds were deformed differently by the applied probe force because of their different local rigidity. This change in the elasticity properties can be explained as a consequence of the inclusion process. This method shows that tapping-mode atomic force microscopy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…53 The AFM cantilever probe applies very small-scale forces on the material while it is moving the work piece to scribe the material. 54,55 Figure 9 presents AFM images of GNIS as scanned by microscope probe in tapping mode, chosen to reduce nanocutting, 56 under ambient conditions where Figure 9a provides a cross-sectional topographic image of the sample in 2D. Unlike other characterization techniques, AFM can produce 3D images with the particular stacking and height of the nanoparticles as shown in Figure 9b, displaying the topology of the GNIS nanoparticles with the nanoscale.…”
Section: Acs Applied Materials and Interfacesmentioning
confidence: 99%
“…53 The AFM cantilever probe applies very small-scale forces on the material while it is moving the work piece to scribe the material. 54,55 Figure 9 presents AFM images of GNIS as scanned by microscope probe in tapping mode, chosen to reduce nanocutting, 56 under ambient conditions where Figure 9a provides a cross-sectional topographic image of the sample in 2D. Unlike other characterization techniques, AFM can produce 3D images with the particular stacking and height of the nanoparticles as shown in Figure 9b, displaying the topology of the GNIS nanoparticles with the nanoscale.…”
Section: Acs Applied Materials and Interfacesmentioning
confidence: 99%
“…Dynamic AFM modes, tapping-mode AFM among them, were developed to improve lateral resolution and minimize sample distortion or damage (Martin et al, 1987;Hansma and Hoh, 1994;Putman et al, 1994;Anselmatti et al, 1994). A large variety of biomolecules, cells, and molecule-molecule interactions have been studied by tapping-mode AFM in air and liquid environments (Henderson, 1994;Fritz et al, 1995Fritz et al, , 1997Valle et al, 1996;Muñoz-Botella et al, 1996;Samori, 1998;Margeat et al, 1998). However, in most cases tapping-mode images of individual proteins are unable to reveal the fragments or subunits forming the molecule.…”
Section: Introductionmentioning
confidence: 99%
“…In imaging biological materials, TMAFM offers an important advantage over conventional contact-mode AFM: biological molecules and live cells can be imaged directly without the use of any complicated chemical methods to immobilize biological samples onto the substrate and, thus, the structure and function of biomolecules and cells can be studied at the same high level of resolution. Despite the recent success of TMAFM in imaging biological molecules and cells (Henderson, 1994; Hoh, 1994; Lal and John, 1994;Putman et al, 1994;Radmacher et al, 1995;Walivaara et al, 1995;Munoz-Botella et al, 1996;Schabert and Rabe, 1996; You and Lowe, 1996a), there are some basic aspects of TMAFM imaging of biological samples that are still not well understood, for instance, the factors determining the loading force applied to the sample, the deformation of biological samples, and most importantly, the image contrast mechanism(s). Because of the unexpected complexity of TMAFM, there have been few theoretical and experimental studies of the image contrast mechanism(s) (Putman et al, 1994;Hoper et al, 1995;Radmacher et al, 1995;Spatz et al, 1995;Chen et al, 1996;Ho and West, 1996;Howard et al, 1996;Munoz-Botella et al, 1996;Schabert and Rabe, 1996;Tamayo and Garcia, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Recently it has been reported that the frequency-dependent viscoelastic properties of the sample play an important role in determining the success and contrast of TMAFM imaging of biological samples (Putman et al, 1994;Radmacher et al, 1995;Munoz-Botella et al, 1996;Schabert and Rabe, 1996). In this work we have designed a simple system for studying the effect of the protein adsorption at the cantilever on the image contrast of TMAFM.…”
Section: Introductionmentioning
confidence: 99%